Rethinking the Temporary, Reconstituting the Citizen: Rights Mobilization by Temporary Foreign Workers in Comparative Perspective - Venkatesh, Vasanthi (UC Berkeley, 2018)
Workers with temporary immigration status have become the economic reality in several countries, as these workers provide a temporally mobile, cheap workforce that is responsive to economic vicissitudes and anti-immigration sentiment. Temporary foreign workers (TFWs) in low-wage sectors such as agriculture are tied to a single employer, have no access to their family and to permanent residence, and face overwhelming barriers in accessing justice. TFWs spend years residing and working outside of their country of nationality and are unable to be self-sovereign agents either in their countries of origin (because of lack of residence) or in their countries of sojourn (because of lack of nationality). While there have been instances where TFWs were able to make individual legal claims for labor violations in the country of sojourn, collective mobilization against the TFW program itself is exceptional. Collective mobilization represents acting as (partial) citizens, as the claims resemble self-determination claims on behalf of the entire TFW collectivity. How do TFWs and their allies, against all odds, mobilize the law to make collective claims and produce citizenship from below?In this research, I critically examine Israel and Canada, countries that have very similar TFW programs in agriculture but represent two contrasting types of legal mobilization against these programs. Israel is a case of “top-down” constitutional litigation where the results were court-ordered changes to the TFW program. Canada represents a case of legal mobilization “from below” where law is used subversively as a tool for larger political action. What explains the different pathways to legal mobilization in Israel and Canada?In addition to contributing new empirical data and theoretical conceptualizations of the different ways in which the law can be mobilized, my dissertation combines legal mobilization and social movement theories to offer an analytical framework to understand what affects the type of legal mobilization. TFW mobilization is situated in two broad social movements, labor movements and migrant rights/citizenship movements. I frame legal mobilization in the TFW context as a form of anti-hegemonic, contentious collective action and show the complex interactions between the political and discursive environment (political opportunity structure), the legal environment, and the support structure for mobilization (resource organizations).I show that despite barriers to access and courts' unwillingness to overturn immigration law, the law can be collectively mobilized on behalf of TFWs. The pathways to legal mobilization depend on legal opportunities and type of resource support. Constitutional litigation is initiated by cause-driven lawyers or legal organizations, but their framing of issues is constrained. Grassroots, solidarity organizations, in contrast, use the law as a tool for the broader goals of worker mobilization and social change. With the support of such organizations, TFWs are able to articulate their demands collectively, engage in direct action and political mobilization, and demand changes to the TFW program. My comparative historical analysis of Israel and Canada shows that legal and discursive strategies, however, depend on the historical political legacies and current political and economic environments. Elite power and ideological discourses are entrenched and distributed in the context of TFW programs. Political contestation impacts constitutional challenges as well as grassroots mobilization. My dissertation further adds to citizenship theory in three ways. First, it disrupts prevalent myths about the agency of TFWs and their lack of rights consciousness. Second, it offers the possibilities for meaningful change to TFW programs and advances an agentic theory on access to citizenship. Lastly, it adds grist to the conception of “citizenship from below” through the evidence of jurisgenerative practices of TFWs.
Keywords: Vasanthi Venkatesh